Analysis of the Implementation of Ibnu Malik's Al Fiyah Learning at the Hikmatul Ulum Asysyarifuddin Islamic Boarding School - Wildan Mahmudin; Nadia Kurnia Fauziah; Mada Sumringah Sari; Andewi Suhartini; Hasan Basri (al-Afkar, Journal For Islamic Studies, 2025)
Learning the book Al-Fiyah Ibn Malik in Islamic boarding schools is one of the important aspects of Islamic religious education in Indonesia. This book, written by Ibn Malik, contains the basic rules of Arabic, especially in the fields of nahwu (grammar) and sharf (the science of word changes). In the context of Islamic boarding school education, learning Al-Fiyah not only focuses on mastering Arabic theory, but also becomes a means to deepen religious texts in Arabic, such as the Qur'an and Hadith. Therefore, the implementation of learning al-Fiyah in Islamic boarding schools has a very strategic role in improving religious understanding and Arabic language skills of students. This research is a combination of library research and field research. Learning Al-Fiyah Ibn Malik at the Hikmatul Ulum AsySyari'Fuddin Islamic Boarding School in Tasikmalaya City uses two methods, namely sorogan and bandongan. The obstacles faced during the learning process are: 1) difficulty in memorizing verses of poetry; 2) Time constraints; 3) Differences in student ability levels. Some of these obstacles are overcome with an individual approach and gradual teaching.